Average hourly earnings for employees paid by the hour (SEPH), unadjusted for seasonal variation, for selected industries classified using the North American Industry Classification System (NAICS) - Statistics Canada (Government of Canada, 2017)
This table contains 4288 series, with data for years 1991 - 2000 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (13 items: Canada; Newfoundland and Labrador; Nova Scotia; Prince Edward Island ...), Overtime (2 items: Including overtime; Excluding overtime ...), North American Industry Classification System (NAICS) (366 items: Industrial aggregate excluding unclassified businesses; Goods producing industries; Forestry; logging and support ...).